1998
DOI: 10.1001/jama.280.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Press Releases of Science Journal Articles and Subsequent Newspaper Stories on the Same Topic

Abstract: tential public health implications in Web sites. In an era in which information on health matters is disseminated rapidly by the media, circulation of information within the scientific community should be at least as fast, while preserving the quality and reliability of scientific journals. This work was performed as a part of Ricerca Corrente degli Istituti di Ricovero e Cura a Carattere Scientifico, 1997.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 4 publications
6
63
0
4
Order By: Relevance
“…Good science communication not only highlights research findings, but places those findings in a context that the target audience can understand and appreciate. Studies have found that public relations in general, and news releases in particular, have an impact on which studies reporters choose to cover [7,8]. And researchers have also found that a good news release about research findings can actually improve the quality of the information that appears in subsequent news stories [9].…”
Section: Public Communication and Public Relationsmentioning
confidence: 99%
“…Good science communication not only highlights research findings, but places those findings in a context that the target audience can understand and appreciate. Studies have found that public relations in general, and news releases in particular, have an impact on which studies reporters choose to cover [7,8]. And researchers have also found that a good news release about research findings can actually improve the quality of the information that appears in subsequent news stories [9].…”
Section: Public Communication and Public Relationsmentioning
confidence: 99%
“…Tras la tergiversación y manipulación informativa se albergan otros intereses de distinta índole (aparte de los económicos, ya sean personales o por la búsqueda de financiación): notoriedad y aumento vertiginoso de las acciones de las empresas que financian esas investigaciones (De Semir et al, 1998), ajenos a la buena práctica de los científicos y de los periodistas que se encargan de estos temas, que distorsionan de manera consciente la labor veraz y transparente de los medios informativos. Hay que indicar también que estos intereses afectan tanto a los periodistas como a los científicos.…”
Section: Políticas De Investigación Biomédicaunclassified
“…While signaling recognition that the process of science communication was significantly more complex than the direct interaction between scientists and journalists implied, the linear transmission model and associated notions of science communication as 'flow' and 'translation' continue to feature strongly (de Semir et al, 1998;Saguy and Almeling, 2008;Brechman et al 2009 and 2011), particularly in health communication research (Hallin and Briggs, 2015).…”
Section: Accuracy In News Journalism Studiesmentioning
confidence: 99%